2015
DOI: 10.1371/journal.pone.0134396
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor β Agonists Differentially Affect the Growth of Human Melanoma Cell Lines

Abstract: BackgroundCutaneous melanoma is an aggressive malignancy; its incidence is increasing worldwide and its prognosis remains poor. Clinical observations indicate that estrogen receptor β (ERβ) is expressed in melanoma tissues and its expression decreases with tumor progression, suggesting its tumor suppressive function. These experiments were performed to investigate the effects of ERβ activation on melanoma cell growth.Methods and ResultsProtein expression was analyzed by Western blot and immunofluorescence assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 81 publications
1
49
0
Order By: Relevance
“…In line with these clinical observations, we recently demonstrated that ERβ, but not ERα, is the ER expressed in human melanoma cell lines, harboring different genetic mutations (A375, BLM, WM115, and WM1552) (110). Moreover, the pattern of expression of the different ERβ isoforms was similar in BLM (NRAS-mutant, BRAF-wild type) and WM115 (BRAF V600D-mutant) melanoma cells: ERβ1 and ERβ5 were found to be expressed at similar levels while ERβ2 showed a higher level of expression.…”
Section: Estrogen Receptor β and Melanomasupporting
confidence: 60%
See 2 more Smart Citations
“…In line with these clinical observations, we recently demonstrated that ERβ, but not ERα, is the ER expressed in human melanoma cell lines, harboring different genetic mutations (A375, BLM, WM115, and WM1552) (110). Moreover, the pattern of expression of the different ERβ isoforms was similar in BLM (NRAS-mutant, BRAF-wild type) and WM115 (BRAF V600D-mutant) melanoma cells: ERβ1 and ERβ5 were found to be expressed at similar levels while ERβ2 showed a higher level of expression.…”
Section: Estrogen Receptor β and Melanomasupporting
confidence: 60%
“…The activity of ERβ agonists was accompanied by an altered expression of the proteins involved in the G1/S transition of the cell cycle (decreased levels of cyclin D1 and cyclin D3, and increased expression of p27, a CDK inhibitor); the apoptosis pathway was not involved in this activity (no change in the cleaved, active form of caspase-3). Importantly, we reported an aberrant global DNA hypomethylation in BLM cells, indicative of genome instability; ERβ activation reverted this hypomethylation status (110). Taken together, these data demonstrate that, in NRAS-mutant melanoma cells, ERβ is associated with an antitumor activity, by causing cell cycle arrest and through the regulation of cell cycle-associated proteins; similar observations were previously reported in different types of cancers expressing this receptor (94, 101, 134140).…”
Section: Antitumor Activity Of Erβ In Melanomamentioning
confidence: 90%
See 1 more Smart Citation
“…Melanoma lacks significant oestrogen receptor alpha (ERα) expression, the receptor responsible for the proliferative effects of oestrogen on breast cancer. However, prior reports have demonstrated high oestrogen-receptor beta (ERβ), which may have anti-proliferative activity, 28 in primary melanoma, 29 as well as non-classical oestrogen signaling through a G-protein coupled oestrogen receptor (GPER). 30 Recent studies suggest that GPER signaling in melanocytes may regulate their differentiation status, 30 which has been implicated in resistance to both targeted and immune therapy in this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Real-time PCR was performed as previously described57. Briefly, real-time DNA amplification was performed in CFX96 Bio-Rad using 20 μl of total volume.…”
Section: Methodsmentioning
confidence: 99%